Treatment of Pediatric Intercondylar Humerus Fracture With External Fixation and Percutaneous Pinning After Closed Reduction - Shu, Wen; Zhao, Rong; Yang, ZiMo; Li, XiangRui; Jiang, GuoYong; Rai, Saroj; Zhong, Haobo; Tang, Xin (Frontiers in Pediatrics, 2022)
Background: It is uncommon for young children to suffer an intercondylar fracture of the distal humerus. Although many approaches have been described to manage, there is no specific and accepted treatment protocol for such fracture patterns. This study aims to identify the incidence of intercondylar fracture of the distal humerus in the pediatric population and report the clinical outcome of external fixation and percutaneous pinning in such injury patterns. Methods: Pediatric patients under the age of 14 years who had an intercondylar fracture of the distal humerus treated with external fixation and percutaneous pinning between January 2013 and December 2018 at the author’s institute were retrospectively evaluated. The detailed baseline information of the patients, operating time, time to union time, and carrying angle difference (CAD) of the injured extremity were collected. During the follow-up visit, clinical results were evaluated using the Mayo Elbow Performance Score (MEPS) and Flynn criteria. Results: Eight patients (2 females and 6 males) with an average age of 8 years old (5 to 12 years) who had intercondylar fracture of the distal humerus (1 C2 and 7 C1) were included. All the patients achieved union and the average MEPS score was 95 points 24 months after the surgery. Conclusions: The intercondylar fracture of the distal humerus in children is rare, and closed reduction and external fixation is a viable treatment option, especially for the C1 type of fracture pattern.